Unveiling a proton-coupled electron-transfer mechanistic library of nitrate to ammonia via ultramicroelectrode-hyphenated mass spectrometry - Xiang Zhao; Chaoyue Gu; Junjie Liu; Bingjie Kong; Sen Liang; Yang Tian; Hongbing Fu; Yuanhua Shao (Proceedings of the National Academy of Sciences, 2026)
For valuable ammonia synthesis and green nitrogen recycling, electrocatalytic nitrate reduction reaction (NO 3 RR) presents a sustainable alternative to the conventional Haber–Bosch process. The NO 3 RR involves intricate, multi-step proton-coupled electron transfers (PCET) featuring multiple nitrogen-oxygen intermediates and reaction branches. Unveiling this complex reaction library is crucial for rational tailoring of NO 3 RR for improved practical application, yet it remains a formidable challenge. Herein we present an in situ ultramicroelectrode-hyphenated mass spectrometry technique to systematically investigate the dynamic electrocatalytic NO 3 RR, using a cobalt-based molecular catalyst as a model system, and to decipher its mechanistic library under complex reaction environments (potential- and pH-dependent). Several key short-lived CoNO x H y intermediates were directly tracked and identified, experimentally revealing that the overall catalytic pathway of NO 3 RR proceeds through the intermediary [LCo-NO 3 ]→[LCo-NO 3 H] + →[LCo-NO 2 ] + → [LCo-NO 2 H] + → [LCo-NO] + → [LCo-NHOH] + → [LCo-NH] + to produce NH 3 , which were further validated by isotopic 15 N-labeling and collision-induced dissociation experiments. Combining theoretical simulations, a complete PCET-based mechanistic pathway was elucidated and distinguished from competing hydrogenation–deoxygenation mechanisms. Notably, a systematically interconnected electrochemical mechanistic library for NO 3 RR, visualized through heat maps, was constructed to illustrate intermediate selectivity across a broad potential-pH space. This platform underscores the promising potential of navigating the pathway prediction and regulation of complex reaction environments, thereby advancing the mechanistic understanding of NO 3 RR and other complicated electrocatalytic processes.